Introduction to Dossier: Lessons from Latin America on the rational choice, cognitive and institutional approaches to policy change - Fontaine, Guillaume (Íconos)
A review of the pertinent academic literature identifies three analytical focuses in studies of policy change. Rational choice- with its theories of incrementalism, multiple currents and punctuated equilibrium- privilege the decision-making process and the rational nature of the individual actor. The cognitivists- with their framework of promoter coalitions, the theory of social/ global references and critical theory- emphasize the presentation of policy problems and the legitimating discourse behind the decision-making process. The neo-institutionalist- with their theories of the logic of the adequate, path dependence and the three-order process of policy change- emphasize the importance of formal and informal institutions in the development of public policies.